Reconstruction Of Humanistic Education In The Era Of Society 5.0 - Maulana, M. Firman; Rosmidar, Rosmidar; Permata, Risky Ayu; Anshary, Chaliza (Al-Fikru: Jurnal Ilmiah, 2025)
The era of Society 5.0 has brought fundamental transformations to education through the integration of intelligent technologies oriented toward human well-being. However, in practice, this development also generates serious challenges, particularly the potential dehumanization of education due to the dominance of technology and instrumentalistic approaches to learning. This article aims to examine the urgency and direction of reconstructing humanistic education in responding to the era of Society 5.0 through dialogue and synthesis of humanistic and critical educational thought. This study employs a qualitative–conceptual literature review method, utilizing critical analysis of educational, humanities, and Society 5.0-related literature. The findings indicate that humanistic education plays a strategic role as a value-based foundation in maintaining a balance between technological advancement and the strengthening of human dimensions in education. The reconstruction of humanistic education in the era of Society 5.0 involves reorienting educational goals, transforming the role of educators, developing dialogical and reflective learning processes, and internalizing ethical values, empathy, and social responsibility. This article is expected to provide a conceptual foundation for the development of future educational paradigms that are adaptive to technological change while remaining firmly oriented toward human values.